Effects of oral Lcarnitine supplementation on liver enzymes in pediatric acute lymphoblastic leukemia patients in the maintenance phase of treatment: a randomized clinical trial study - Eghbali, Aziz; Eghbali, Aygin; Ashayeri, Neda; Fadayi, Fatemeh; Ghaffari, Kazem; Ghasemi, Ali (Frontiers in Pharmacology, 2025)
BackgroundGiven that liver diseases and subsequent increases in liver enzymes are among the most frequent complications observed in leukemia patients treated with chemotherapeutic drugs, this study aimed to assess the impact of oral Lcarnitine supplementation on liver enzyme levels the maintenance phase of treatment for pediatric acute lymphoblastic leukemia (ALL) patients.MethodsIn this clinical trial, 100 pediatric patients aged >5 years were divided into two groups after obtaining informed consent. The participants were randomly divided into the Lcarnitine and placebo groups. In the Lcarnitine group, patients received 50 mg/kg of Lcarnitine syrup three times a day (every 8 h). Patients were examined for 2 months to receive Lcarnitine syrup and to measure the levels of alanine aminotransferase (ALT), aspartate transferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), direct bilirubin, total bilirubin, prothrombin time (PT), and partial thromboplastin time (PTT).ResultsThe mean changes in AST, ALT, total bilirubin, and GGT during the study period were significant in the group treated with Lcarnitine (P < 0.05), although they were not significant in the placebo group (P > 0.05). Also, the levels of ALP, direct bilirubin, PT, and PTT were not significantly different between the two groups. The incidence of side effects was significantly higher in the Lcarnitine group than in the placebo group (18% vs 4%, P = 0.025).ConclusionThe results of this study suggested that a 60-day Lcarnitine treatment can improve liver enzyme levels and thus prevent the extent of liver damage during the treatment of ALL. Based on the results of our study, Lcarnitine supplementation may have a beneficial effect on liver enzyme levels in pediatric ALL patients during the maintenance phase of treatment.Clinical Trial Registration:https://irct.behdasht.gov.ir/search/result?query=IRCT20201107049296N2, identifier IRCT20201107049296N2